P-316 Awareness and practices regarding 'long COVID' among employees of selected electronics industries in South India. (14th March 2023) - Joseph, Merlyn; Joseph, Bobby
Abstract : Introduction: 'Long COVID' is a term coined for long term post COVID-19 disease complications. Touted as the 'pandemic after the pandemic' it has significant implications for employment especially on productivity and quality of worker output. Objectives: 1. To assess the baseline knowledge among employees working in selected electronics goods manufacturing companies regarding COVID-19 disease, COVID vaccination and long COVID complications. 2. To assess the prevalence of long COVID complications among the study subjects. Methodology: We followed a quantitative cross-sectional study design between May-Jun 2022 in 6 factories across South India. A semi-structured, face-validated interview schedule was administered to the employees via Google Forms®. Data was analysed using SPSS v.21. Results: A total of 118 employees were included in the study. Most employees were male (89.2%), between 25–30 years of age (46.3%) and had completed their bachelor's degree (71.29%). Most had at least 1–5 years of current work experience (80.5%). Almost 55.1% of the employees had suffered from COVID-19 in the past of whom 33.8% had been hospitalised. Only 42.8% of employees knew about long COVID complications and 33.1% knew of only one symptom. None of the employees had taken the booster dose of the vaccine despite 67.8% knowing that the vaccine protected against severe disease. Almost 75% of employees reported to suffer from one or more post COVID complications. Long standing fatigue (16.9%), cough and breathing difficulty (6.1%) were the most common complaints. Conclusion: Low awareness regarding long COVID will impact health seeking behaviour and increase presenteeism at the workplace. Increasing awareness regarding COVID-19 disease, vaccinations and the post COVID complications through training programmes and health education sessions will bridge the key knowledge gaps identified. Promotion of booster dose vaccination against COVID-19 for all employees will help in reducing the burden of long COVID at the workplace.